Sound absorption qualities of a cylinder-shaped isolated acoustic resonator - Stauskis, V. (Journal of Civil Engineering and Management, 1995)
In the article, an isolated acoustic resonator consisting of a cylinder-shaped hole of variable volume and with large and variable diameter is theoretically analyzed. Theoretical formulaes by which sound absorption of such resonator is computed are presented. The computations incorporate the influence exerted by overtones, i.e. odd harmonics, and supplementary resonator mass upon sound absorption. A change in the sound absorbtion depending on the resonator hole diameter, the angle of sound wave incidence and its volume, i.e. the distance to the rigid surface, has been established. Sound absorption reaches its maximum at low frequencies and it depends strongly on the hole diameter. Under constant hole diameter, sound absorption does not depend on the resonator volume, i.e. the distance to the rigid surface. Absorption notably depends on the angle of sound wave incidence. When this angle increases, absorption also increases at resonant frequency, while the frequency itself moves towards higher frequencies. When the sound wave incidence is 90 degrees with respect to resonator, maximum absorption is already observed at high frequencies. Real and imaginary parts of the radiation impedance of cylindric hole and of the impedance of the hole itself, as well as their dependency on frequency are computed. In this case, hole impedance consists of the impedances of the hole and air resiliency. The influence exerted by the real and imaginary parts upon sound absorption has been established. The resonance takes place when the imaginary parts of radiation and hole impedances intersect. Article in Lithuanian. Cilindrinės formos vienetinio akustinio rezonatoriaus garso absorbcinės savybės First Published Online: 26 Jul 2012